EFEKTIVITAS PENGGUNAAN MEDIA KOMIK PADA KETERAMPILAN MENULIS LAGU GUBAHAN MENGGUNAKAN RIMA PADA PEMBELAJARAN BAHASA INDONESIA PESERTA DIDIK KELAS IV B SD NEGERI BONDONGAN KOTA BOGOR - Dede Nora Sumirat; Fitri Siti Sundari; Siti Nurjanah (STKIP Subang, 2024)
This study evaluates the effectiveness of comic media in improving song writing skills using rhymes of fourth grade students at SD Negeri Bondongan, Bogor city, using a descriptive qualitative approach. The research methods included classroom observation, interviews, and document analysis of 28 learners. The results show that the use of comic media is effective in improving songwriting skills using rhyme. In the observation, students were actively involved in working on the LKPD observing comic media as a medium for writing compositional songs using rhyme. Interviews showed that they were motivated and enthusiastic. Document analysis showed a significant improvement in learners' writing after using comic media. Thus, it shows that the use of comic media can be a good choice in learning Indonesian to improve the skill of writing songs using rhymes of grade IV students.